Patients’ experiences and practices of medication literacy in inflammatory bowel disease: a qualitative study - Pan, Wanya; Tian, Wenhao; Li, Shuyan; Zhao, Yuan; He, Yan; Liu, Yanjie; Feng, Xiuqin (Frontiers in Pharmacology, 2026)
BackgroundMedication literacy is critical for the safe and effective use of medications. Patients with inflammatory bowel disease (IBD) face complex and evolving medication regimens. However, little is known about medication literacy in this population. This study aimed to explore the experiences and practices of patients with IBD to characterize their current level of medication literacy.MethodsA descriptive qualitative research design was adopted. From November 2024 to January 2025, adult patients with IBD were recruited using purposive sampling at a tertiary hospital in China. One-on-one semi-structured interviews were conducted with the patients. All interviews were audio-recorded and transcribed verbatim. The data were analyzed using directed content analysis.ResultsQualitative analysis of 16 patients revealed the following characteristics across the five core competencies of medication literacy: (1) Accessing medication information: patients were able to obtain information through various channels, primarily healthcare professionals and the internet, but they were not always proactive in seeking it. (2) Understanding medication information: patients knew the names and dosages of their medications, but their understanding of the reasons for long-term use, treatment-plan adjustments, and monitoring indicators was relatively superficial. (3) Communicating medication information: patients were able to talk with healthcare professionals, but their involvement in shared decision-making was limited and they rarely communicated with fellow patients. (4) Evaluating medication information: patients assessed the credibility of information according to the authority of the source, yet found it difficult to judge accuracy on the basis of their own knowledge. (5) Calculating medication information: patients demonstrated strong ability in calculating dosing times and amounts, although they occasionally relied on external tools to ensure accuracy.ConclusionPatients with IBD demonstrate a basic level of medication literacy but face challenges across all five dimensions of medication information processing. Findings of this study highlight key components of medication literacy that require development and may provide a foundation for designing targeted assessments and personalized health education programs.